Design of a High Resolution, Monolithic Crystal, PET/MRI Detector with DOI Positioning Capability - Miyaoka, Robert S. (2008)
We report on a high resolution, monolithic crystal PET detector design concept that provides depth of interaction (DOI) positioning within the crystal and is compatible for operation in a MRI scanner to support multimodal anatomic and functional imaging. Our design utilizes a novel sensor on the entrance surface (SES) approach combined with a maximum likelihood positioning algorithm. The sensor will be a two-dimensional array of micro-pixel avalanche photodiodes (MAPD). MAPDs are a new type of solid-state photodetector with Geiger mode operation that can provide signal gain similar to a photomltipiler tube (PMT). In addition, they can be operated in high magnetic fields to support PET/MR imaging. Utilizing a multi-step simulation process, we determined the intrinsic spatial resolution characteristics for a variety of detector configurations. The crystal was always modeled as a 48.8 mm by 48.8 mm by 15 mm monolithic slab of a lutetium-based scintillator. The SES design was evaluated via simulation for three different two-dimensional MAPD array sizes: 8×8 with 5.8×5.8 mm(2) pads; 12×12 with 3.8×3.8 mm(2) pads; and 16×16 with 2.8×2.8 mm(2) pads. To reduce the number of signal channels row-column summing readout was explored for the 12×12 and 16×16 channel array devices. The intrinsic spatial resolution for the 8×8 MAPD array is 0.88 mm FWHM in X and Y, and 1.83 mm FWHM in Z (i.e., DOI). Comparing the results versus using a conventional design with the photosensors on the backside of the crystal, an average improvement of ~24% in X and Y and 20% in Z is achieved. The X, Y intrinsic spatial resolution improved to 0.66 mm and 0.65 mm FWHM for the 12×12 and 16×16 MAPDs using row-column readout. Using the 12×12 and 16×16 arrays also led to a slight improvement in the DOI positioning accuracy.